The emotional significant negative events and wellbeing of student teachers during initial teacher training: The case of physical education - Descoeudres, Magali; Cece, Valérian; Lentillon-Kaestner, Vanessa (Frontiers in Education, 2022)
Teaching is a demanding job and the aim of the present study was to explore the emotional experiences and well-being levels (burnout and vigour) of Physical Education (PE) student teachers in comparison with student teachers of other subjects. In all, 167 student teachers (99 in PE and 68 in other subjects) described two significant professional negative events experienced during the school placement. They also reported the frequency of occurrence of these events, the level of unpleasant emotions related to the events, and their scores of burnout and vigour. The negative emotional events were encoded following an inductive approach and five categories emerged: Student rules violations, Collaborative issues, Physical integrity risks, Organizational issues and Lack of student motivation. The Chi-square analyses revealed a different distribution in the negative events according to the subject taught, especially including an overrepresentation of Lack of student motivation and Physical integrity risks for PE student teachers and Collaborative issues for other-subjects student teachers. Moreover, Mann-Whitney U tests revealed a similar frequency of negative emotional events whatever the subject taught, but a lower intensity of unpleasant emotions, lower physical fatigue and higher scores of physical strength for PE student teachers in comparison with those of other subjects. The present findings confirmed that the specificities of PE lead to singular significant negative events for PE students during initial training. Finally, the health outcomes (intensity of unpleasant emotions, burnout and vigour) suggest that PE teachers have developed specific resources to cope with school constraints, probably in relation to their sport experiences.